2011
DOI: 10.1145/2070781.2024173
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid iterative solver for robustly capturing coulomb friction in hair dynamics

Abstract: Dry friction between hair fibers plays a major role in the collective hair dynamic behavior as it accounts for typical nonsmooth features such as stick-slip instabilities. However, due the challenges posed by the modeling of nonsmooth friction, previous mechanical models for hair either neglect friction or use an approximate smooth friction model, thus losing important visual features. In this paper we present a new generic robust solver for capturing Coulomb friction in large assemblies of tightly packed fibe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(40 citation statements)
references
References 44 publications
0
37
0
Order By: Relevance
“…Such simulations were for long limited in complexity and resolution due to computational overhead. Recently, some authors demonstrated that the simulation of thousands guide strands subject to complex hair-body and hair-hair interactions was now affordable on a standard desktop computer [Selle et al 2008;McAdams et al 2009;Daviet et al 2011].…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…Such simulations were for long limited in complexity and resolution due to computational overhead. Recently, some authors demonstrated that the simulation of thousands guide strands subject to complex hair-body and hair-hair interactions was now affordable on a standard desktop computer [Selle et al 2008;McAdams et al 2009;Daviet et al 2011].…”
Section: Related Workmentioning
confidence: 99%
“…This format indeed corresponds to the standard output produced by hair designing tools and recent hair capture systems. Furthermore, representing hair with curves is in line with the input of the most advanced hair animation systems, which often simulate a discrete assembly of guide strands [Hadap 2006;Selle et al 2008;McAdams et al 2009;Bergou et al 2010;Daviet et al 2011].…”
Section: D Geometric Fittingmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, hair-body and hair-hair contacts have been more accurately modeled by using a non-smooth Newton solver for the Coulomb friction law . Daviet et al [2011] globally solves for Coulomb friction with a hybrid Gauss-Seidel algorithm, using an analytic solver to ensure convergence.…”
Section: Related Workmentioning
confidence: 99%